Reasons for seagrass optimism: Local ecological knowledge confirms presence of dugongs. (September 2018) - Cullen-Unsworth, Leanne C.; Jones, Benjamin L.; Seary, Rachel; Newman, Rhian; Unsworth, Richard K.F.
Abstract: Dugongs ( Dugong dugon ) depend on seagrass meadows for food. As such seagrass and dugong conservation should go hand in hand. Assessing dugong populations is notoriously challenging. In the most resource dependent communities Local Ecological Knowledge (LEK) is generally high and can provide an alternative to the use of expensive ecological surveys to understand dugong populations and support associated resource management decisions. Residents of the Wakatobi National Park (WNP), SE Sulawesi, Indonesia are highly dependent on marine resources for livelihoods and correspondingly LEK is high. Here LEK documents the presence of D. dugon in the WNP and infers changes in population size. Interviews with local residents in 2012–2013 revealed 99 sightings of dugongs since 1942, 48 of which occurred between 2002 and 2012, with 79.82% of respondents having seen a dugong. Declines in the frequency of sightings within the lifetime of several respondents were reported, respondents speculating that populations are reduced. This information can guide further cooperative research and conservation efforts for the protection of a vulnerable species and the seagrass habitat on which it depends. Highlights: Local Ecological Knowledge (LEK) evidences presence and population change of Dugong dugon in the Wakatobi National Park Persistence of D. dugon in the park provides a reason to be optimistic about the status of Wakatobi seagrass meadows Clear pathway for integration of LEK into management planning for D. dugon and the seagrass meadows on which they depend